2010
DOI: 10.1002/esp.1929
|View full text |Cite
|
Sign up to set email alerts
|

Coupling mechanisms in double sandbar systems. Part 1: patterns and physical explanation

Abstract: Crescentic sandbars and rip channels along wave-dominated sandy beaches are relevant to understand localized beach and dune erosion during storms. In recent years, a paradigm shift from hydrodynamic template models to self-organization mechanisms occurred to explain the formation of these rhythmic features. In double sandbar systems, both the inner-and outerbar rip channels and crescentic planshapes are now believed to be free instabilities of the nearshore system arising through selforganization mechanisms al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
113
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(137 citation statements)
references
References 49 publications
12
113
0
3
Order By: Relevance
“…The inner and outer bar systems exhibit an out-of-phase relationship with the landward pointing horns of the outer bar coinciding with the seaward pointing salients associated with the inner bar system. A similar configuration was found by Price and Ruessink (2011) along the double-barred Gold Coast in Australia and is attributed to the dominance of parallel wave approach (Castelle et al, 2010a, b). Compared to other beaches described in the literature, Perranporth is most similar to Truc Vert (Castelle et al, 2007;Senechal et al, 2009;Coco et al, 2014), although the latter beach is characterised by more energetic wave conditions and a smaller tide range.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The inner and outer bar systems exhibit an out-of-phase relationship with the landward pointing horns of the outer bar coinciding with the seaward pointing salients associated with the inner bar system. A similar configuration was found by Price and Ruessink (2011) along the double-barred Gold Coast in Australia and is attributed to the dominance of parallel wave approach (Castelle et al, 2010a, b). Compared to other beaches described in the literature, Perranporth is most similar to Truc Vert (Castelle et al, 2007;Senechal et al, 2009;Coco et al, 2014), although the latter beach is characterised by more energetic wave conditions and a smaller tide range.…”
Section: Discussionsupporting
confidence: 66%
“…Upstate (3D to 2D; offshore migration) and downstate (2D to 3D; onshore migration) transitions occur under increasing and decreasing wave energy conditions, respectively (Short, 1979;Lippmann and Holman, 1990;Ranasinghe et al, 2004;Poate et al, 2014), although longshore currents are also thought to play a role in straightening bar morphology (Price and Ruessink, 2011). There is also morphodynamic feedback between the outer and inner bar system; specifically, the outer bar protects the inner bar from energetic wave actions (Coco et al, 2014), whilst also controlling wave breaker patterns and nearshore current circulation over the inner bar system, even under less energetic wave conditions (Castelle et al, 2010a, b). According to Price and Ruessink (2011), the outer and inner bar systems are out-of-phase (in-phase) for dominantly parallel wave approach and weak longshore currents (oblique wave approach and strong longshore currents).…”
Section: Introductionmentioning
confidence: 99%
“…These results provide a tentative timescale for the return to 3D morphology. Unfortunately, the lack of subaqueous surveys prevents a definitive statement on the role of the offshore sandbar in providing a template to cause 3D morphology also in the inner sandbar and the shoreline (as shown in Castelle et al, 2010), and in accounting for exchanges of sediment between the outer and inner sandbar (Almar et al, 2010) which could ultimately affect the beachface. Overall, it appears that the development of 3D morphology is associated with calm/accretionary conditions, while 2D morphology results from stormy/erosive conditions (these conditions can not be uniquely defined as they are site-specific and depend on previous hydrodynamic conditions and current beach configuration).…”
Section: Discussionmentioning
confidence: 99%
“…This has long been interpreted as self-organisation at the scale of the individual bar and the absence of interaction between sandbars. Other observations, summarised in Castelle et al (2010a), demonstrate that innerbar patterns can also couple to those in the outer bar, indicative of a type of interaction that Castelle et al (2010a) morphological coupling. Ruessink et al (2007a), for example, found that the inner bar increasingly coupled to the outerbar shape as the outer bar became more crescentic and migrated onshore, i.e.…”
Section: Observationsmentioning
confidence: 99%
“…The genesis of crescentic patterns in single sandbar systems is thus reasonably well understood. In a double sandbar system, with a more landward inner bar and a more seaward outer bar, the distinction between a forcing template and self-organisation becomes blurred (Castelle et al, 2010a, b). In this case, the crescentic outer-bar morphology acts as a morphological template for the inshore flow patterns through the breaking and focussing of waves across the outer bar.…”
Section: Introductionmentioning
confidence: 99%